Biaya Langsung dan Tidak Langsung pada Penyakit Hipertensi: Narrative Review - Budi Respati Nur Mulianingsih; Dwi Endarti; Anna Wahyuni Widayanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Hypertension is a health problem that increases mortality and morbidity and the economic burden of healthcare in Indonesia. Analysis of Cost of Illness (COI) must be conducted from different perspectives to provide additional information for policymakers about the economic impact caused by hypertension. This review aims to explain the components of healthcare costs in hypertension based on different perspectives, namely patient, payer, and healthcare providers. The results of this study show that direct and non-medical costs are the largest component of healthcare costs. Drug, doctor consultations, supporting examinations (laboratory tests), healthcare workers, administration costs are the highest direct medical costs. Travel and food expenses are components of direct non-medical costs. The lost productivity of patients or caregivers is calculated using the human capital approach and occupies health expenses as indirect costs. This can help the government and other researchers have the same perception in determining the components of the health costs under study. A study of COI can help the government control hypertension with promotive and preventive efforts and improve the government's public health program for hypertension.